Mineralogical and Textural Characteristics of Kakul (Hazara) Phosphate Rock, NWFP, Pakistan: Mineralogy of Kakul Phosphate Rock (Biological Sciences - PJSIR, 2010)
Various types of minerals, present in phosphate rock of Hazara area of Khyber Pukhtoonkhwa Province of Pakistan, were identified and their concentration was determined using a suitable method. The characteristics of the rock were defined by petrography, X-ray diffraction, and chemical analysis and the textural characteristics such as grain size, grain shape and their arrangement in the rock body were also investigated. The degree of liberation of phosphate-bearing mineral was studied by the particle-counting method. Mineralogical and textural observations indicated that fine-grained rock may be suitable for beneficiation by the froth flotation  separation   technique.